IS THERE DEMAND FOR ONLINE PHYSICAL EDUCATION NEXT TO IN-PERSON CLASSES? A STUDY OF THE MOTIVATION OF EÖTVÖS UNIVERSITY’S STUDENTS - Katalin Kovács; Ágnes Novák (The Sky)
In the autumn semester of the 2021/22 academic year, Eötvös University offered both online and in-person physical education courses, which were filled within days. The interest of hundreds of students in the online course peaked the educators’ interest in whether there is a difference in the motivation of students who complete the course on-line and those who attend in-person. Of the 14 sub-factors of the EMI-2 motivation scale, only two (affiliation and competition) showed significant differences between the students of the two courses, however when comparing women and men we found significant differences in 7 factors. Regardless of whether the students attended the online or in-person physical education course, their motivations for physical activity were almost the same. Greater differences were observed between the sexes and between former competitive and non-competitive athletes.